Rune Frederiksen, Silke Müth, Peter I. Schneider and Mike Schnelle (eds) Focus on Fortifications. New Research on Fortifications in the Ancient Mediterranean and the Near East - Lohmann, Hans (Journal of Greek Archaeology, 2017)
The present volume – the 2nd of the series ‘Focus on Fortifications’ –, comprises the papers given at an international conference organised by the Danish Institute and the German Archaeological Institute at Athens in the new Acropolis-Museum in December 2012. The total of 57 papers in German, English and French delivered by 73 authors, some of which participated in more than one contribution, spans a wide arc, reaching from the ancient civilizations of the Near and Middle East to the Early Byzantine era and geographically from Syria in the East to Spain in the West and from Gallia in the North to Yemen in the South.